Smooth perfluorinated surfaces with different chemical and physical natures their unusual dynamic dewetting behavior toward polar and nonpolar liquids - Cheng, Dalton F (Langmuir : the ACS journal of surfaces and colloids, 2013)
The effects of surface chemistry and the mobility of surface-tethered functional groups of various perfluorinated surfaces on their dewetting behavior toward polar (water) and nonpolar (n-hexadecane, n-dodecane, and n-decane) liquids were investigated. In this study, three types of common smooth perfluorinated surfaces, that is, a perfluoroalkylsilane (heptadecafluoro-1,1,2,2-tetrahydrooctyl-dimethylchlorosilane, FAS17) monomeric layer, an amorphous fluoropolymer film (Teflon AF 1600), and a perfluorinated polyether (PFPE)-terminated polymer brush film (Optool DSX), were prepared and their static/dynamic dewetting characteristics were compared. Although the apparent static contact angles (CAs) of these surfaces with all probe liquids were almost identical to each other, the ease of movement of liquid drops critically depended on the physical (solidlike or liquidlike) natures of the substrate surface. CA hysteresis and substrate tilt angles (TAs) of all probe liquids on the Optool DSX surface were found to be much lower than those of Teflon AF1600 and FAS17 surfaces due to its physical polymer chain mobility at room temperature and the resulting liquidlike nature. Only 6.0° of substrate incline was required to initiate movement for a small drop (5 μL) of n-decane, which was comparable to the reported substrate TA value (5.3°) for a superoleophobic surface (θ(S) > 160°, textured perfluorinated surface). Such unusual dynamic dewetting behavior of the Optool DSX surface was also markedly enhanced due to the significant increase in the chain mobility of PFPE by moderate heating (70 °C) of the surface, with substrate TA reducing to 3.0°. CA hysteresis and substrate TAs rather than static CAs were therefore determined to be of greater consequence for the estimation of the actual dynamic dewetting behavior of alkane probe liquids on these smooth perfluorinated surfaces. Their dynamic dewettability toward alkane liquids is in the order of Optool DSX >> Teflon AF1600 ≈ FAS17